Design of a Portable Power Plant Using Solar and Wind Energy with Hybrid Charge Control Method - Vrathama, Brenanda Kristian; Silalahi, Lukman Medriavin (CCIT (Creative Communication and Innovative Technology) Journal, 2025)
New Renewable Energy is an environmentally friendly solution for electricity generation, particularly through the utilization of wind and solar energy. In Indonesia, which has a tropical climate, both energy sources can reduce dependence on fossil fuels and carbon emissions. This research aims to design a portable power plant that integrates solar and wind energy using the Hybrid Charge Control method.[1] Testing was conducted at two different locations: Pantai Indah Kapuk 2 (PIK2) and VI Rusun Ujung Menteng. The results showed that in PIK2, the solar power plant reached a peak power of 3.459 W at 1:00 PM, while the wind source produced a peak power of 0.66 W at 5:00 PM. At the Rusun Ujung Menteng location, the highest recorded power from the solar panel was 3.048 W at 2:00 PM, and the wind source reached 0.82 W at 5:30 PM. The use of a DC motor in this system increased the voltage to 4 Volts but also presented issues requiring attention in torque management and cable material selection. The Charge Control method was applied to equalize the battery voltage at a level of 12.4 V. The researchers demonstrated the significant potential of portable renewable energy-based power plants for sustainable energy needs in Indonesia.